2014
DOI: 10.2478/hukin-2014-0073
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Course Length on Individual Medley Swimming Performance in National and International Athletes

Abstract: Effects of course length (25 m versus 50 m) and advances in performance of individual medley swimming were examined for men and women in Swiss national competitions and FINA World Championships during 2000–2011. Linear regression and analysis of variance (ANOVA) were used to analyse 200 m and 400 m race results for 26,081 swims on the Swiss high score list and 382 FINA finalists. Swiss and FINA swimmers of both sexes were, on average, 4.3±3.2% faster on short courses for both race distances. Sex-related differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
1
4
0
2
Order By: Relevance
“…This may be because men gain a larger advantage from a greater number of turns, which offer time for muscle recovery. These findings were in-line with the results reported in Koch-Ziegenbein P. et al 2013 andWolfrum, M. et al 2014, in which breaststroke and medley events were examined rather than freestyle. In Wolfrum M. et al 2013, it was reported that elite female and male freestyle swimmers at national and international levels were about 2% faster on 25m compared to 50m course.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This may be because men gain a larger advantage from a greater number of turns, which offer time for muscle recovery. These findings were in-line with the results reported in Koch-Ziegenbein P. et al 2013 andWolfrum, M. et al 2014, in which breaststroke and medley events were examined rather than freestyle. In Wolfrum M. et al 2013, it was reported that elite female and male freestyle swimmers at national and international levels were about 2% faster on 25m compared to 50m course.…”
Section: Discussionsupporting
confidence: 90%
“…In addition to sex, age, and swimming distance, another factor affecting the performance of a swimmer is the different types of indoor swimming pools which can be either long course metres (LCM, i.e., a pool 50 meters in length) and short courses meters (SCM, i.e., a pool 25 meters in length). While most existing research on swimming performance only considered LCM, there are recent studies that have investigated differences between LCM and SCM, including a study which focused on breaststroke swimming performance of course distances 50m, 100m, and 200m (Koch-Ziegenbein P. et al 2013) and one that examined medley swimming performance of course distances 200m and 400m (Wolfrum, M. et al 2014), both in national and international levels with selected top 10 athletes. Research across short (50 and 100 meters), intermediate (200 and 400 meters), and long (800 and 1500 meters) distances in both LCM and SCM pools is needed to gain an integral understand on sex and age differences of freestyle swimming performance.…”
Section: Volume --| Issue -| 2021 |mentioning
confidence: 99%
“…En concreto, hay diferencias estadísticamente significativas en las tres pruebas analizadas en esta investigación: (p≤0,001) en la prueba 300 metros crol y/o braza, (p≤0,001) en la prueba combinada II y (p=0,019) en la prueba 100 metros rescate con aletas. Estos resultados coinciden con las conclusiones de las investigaciones realizadas en el ámbito de la natación de competición (Keskinen et al, 2007;Koch-Ziegenbein et al, 2013;Lowensteyn et al, 1994;Wolfrum et al, 2013;Wolfrum et al, 2014). En este sentido, resulta paradójico que las instituciones deportivas que organizan sus pruebas acuáticas en vasos de diferentes tamaños, utilicen tablas de conversión para limitar la influencia de la longitud del vaso sobre los resultados deportivos (Real Federación Española Natación, 2016; Real Federación Española Salvamento Socorrismo, 2016) y en cambio, no se han encontrado tablas de conversión que desempeñen esta misma función en el ámbito de la evaluación de los socorristas.…”
Section: Discussionunclassified
“…Un ejemplo de esto que se está señalando, es la ausencia generalizada de tablas de referencia que establezcan la influencia de la longitud del vaso, sobre las marcas de tiempo exigidas a los aspirantes a socorrista en las pruebas físicas de piscina. De hecho, se sabe que las marcas de tiempo obtenidas en las pruebas de natación disputadas en vasos de 25 metros, son significativamente mejores que las que se obtienen en vasos de 50 metros (Keskinen et al, 2007;Koch-Ziegenbein et al, 2013;Wolfrum et al, 2013;Wolfrum et al, 2014). Esto se debe a que las pruebas desarrolladas en vaso de 25 metros, permiten que el deportista realice más virajes y por lo tanto, pueda empujarse más veces en la pared al recorrer una distancia establecida.…”
Section: Introductionunclassified
“…As such, at the beginning of each lap, swimmers achieve velocities far beyond the actual (clean) swimming velocity due to the push-off from the pool wall during each turn 13 . The different pacing pattern and velocity distributions improve short-course performance by 2.0 ± 0.6% for freestyle (FR) and 4.3 ± 3.2% for individual medley (IM) compared to the long-course events 14 , 15 . Therefore, specific reference values for short-course races are required, as they cannot be compared to long-course races.…”
Section: Introductionmentioning
confidence: 99%